2020
DOI: 10.1021/acsomega.0c03105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Hydrotreating Activity of NiW Presulfurized Catalysts Prepared via a Tetrathiotungstate-Intercalated NiAl LDH

Abstract: A tetrathiotungstate-intercalated NiAl layered double hydroxide (LDH) was synthesized and then calcined under N 2 at various temperatures to prepare a series of NiW presulfurized hydrotreating catalysts. Upon calcination, WS 4 2– in the interlayer decomposes into WS 3 and then WS 2 , releasing sulfur to sulfurize nickel in the sheets. The property and activities of catalysts for hydrodesulfurization (HDS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The doublet separation and peak area ratio of two splitting spin-orbits follow the rule reported previously. 10 The corresponding binding energy and percentages of various species are listed in Table 2. The spectrum of S2p consists of two doublets: one at around 162.9 and 161.8 eV assigned to 2p 1/2 and 2p 3/2 of S 2− , the other at around 164.4 and 163.3 eV assigned to 2p 1/2 and 2p 3/2 of S 2 2− .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The doublet separation and peak area ratio of two splitting spin-orbits follow the rule reported previously. 10 The corresponding binding energy and percentages of various species are listed in Table 2. The spectrum of S2p consists of two doublets: one at around 162.9 and 161.8 eV assigned to 2p 1/2 and 2p 3/2 of S 2− , the other at around 164.4 and 163.3 eV assigned to 2p 1/2 and 2p 3/2 of S 2 2− .…”
Section: Resultsmentioning
confidence: 99%
“…A nitrate NiAl LDH with a Ni/Al ratio of 2 denoted as NiAl–NO 3 was used as a precursor to synthesize tetrathiotungstate-intercalated NiAl LDHs via an ion-exchange method. 10 First, 2.4 g ammonium tetrathiotungstate (ATT) that was lab-synthesized as reported previously 11 and 2.0 g NiAl–NO 3 were dispersed in 100 mL water, in which the molar ratio of WS 4 2− to NO 3 − was set to 1. Second, a 10 wt% ammonia solution was added to the suspension to adjust the pH to 8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ammonium tetrathiomolybdate [ATTM, (NH 4 ) 2 MoS 4 ] has attracted significant attention as an established active component for the preparation of catalysts in the sulfuric form (i.e., the presulfided catalysts). ,, It was found that the molybdenum sulfide catalyst prepared by the decomposition of ATTM exhibited a good activity toward thiophene hydrogenolysis. , Catalytic hydrogenolysis activity was directly correlated with the number of anion vacancies and the low valence state of the reduced MoS 2 /Al 2 O 3 catalysts. Moreover, as ATTM has already tetrahedrally bonded to molybdenum atoms, which simplifies the sulfidation of oxide precursors, the decomposition of ATTM will lead to completely sulfided catalysts.…”
Section: Introductionmentioning
confidence: 99%